Isopycnal Mixing in the North Atlantic Oxygen Minimum Zone Revealed by RAFOS Floats - Rudnickas, Donald; Palter, Jaime; Hebert, David; Rossby, H. Thomas (Journal of Geophysical Research: Oceans, 2019)
The Eastern Tropical North Atlantic Oxygen Minimum Zone (OMZ) is a biogeochemically important area. The low oxygen in this region is thought to be maintained by a balance between the slow mixing supply of O2 and its removal by respiration. We use data from 90 isopycnal RAFOS floats to characterize the mixing coefficients responsible for the supply of oxygen to the region. One group was ballasted to drift on the isopycnal where oxygen is at its minimum and the other about 300 m deeper. Using the record of the float positions at each 6-hr interval, we calculate the relative dispersion of pairs of floats. The time derivative of this dispersion provides a diffusivity coefficient that captures the net effect of eddy-driven mixing along each isopycnal. Float pairs deployed at shared locations but across the two target densities reveal that the influence of vertically sheared currents is to accelerate the dispersion by 10–15% relative to true isopycnal dispersion. Relative dispersion of the floats in the OMZ area obeyed the canonical four-thirds power scaling, representative of two-dimensional turbulence. At the length scale of the maximum energy-containing eddy (approximately 100 km), the effective diffusivity is 1,400±500 m2/s in the zonal direction and 800±300 m2/s in the meridional. Within the uncertainty, the diffusivities on the two isopycnals are indistinguishable from one another. An idealized model suggests that meridional mixing across the large-scale O2 gradient is the leading supply term of oxygen to the OMZ.